Sosialisasi Penggunaan QRIS Untuk Mempercepat Transaksi Keuangan Pada Usaha Mikro Kecil - Laila Qadriah; Husaini; Maryanti; Yuswardi; Achmady, Sayed (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
This Community Service Program conducted an outreach initiative for micro and small enterprises to adopt QRIS for the purpose of "Facilitating Financial Transactions," with a case study focused on Micro and Small Enterprises in Sigli City. This program aimed to provide both socialization and hands-on assistance regarding cashless payment systems through the use of QRIS barcodes. The objective of this outreach was to enhance the knowledge of Micro and Small Enterprises about cashless payment systems and their understanding of how to use QRIS to expand their business targets. The program provided insights into cashless payment systems, their benefits, their operational mechanics, and the convenience of transacting through the DANA E-Wallet application. Through this program, Micro and Small Enterprises partners were assisted at every stage: from registering for a personal DANA account, upgrading to DANA Premium and utilizing its fund withdrawal feature, to registering for DANA Business, and finally, generating the QRIS barcode. The results showed that the low level of understanding among Micro and Small Enterprises partners about the developments in cashless payment systems and the use of QRIS barcodes was successfully addressed through the implementation team's outreach. Furthermore, the absence of a support team to guide Micro and Small Enterprises in using QRIS was resolved by this community service program (PKM), conducted by lecturers and students from the Informatics Engineering study program at Jabal Ghafur University, which successfully increased the business owners' interest in the convenience of cashless payment systems.